Evaluation of Adjacent Segment Degeneration after Cervical Spine Surgery: Arthroplasty versus Fusion: - Jangholi, Ehsan; Hamidi, Saeed; Fahimi, Neda; Fahimi, Mohammad Ali; Farshad, Ali; Nazari Foroushani, Farshid; Najibpour, Reza; Yavari, Hassan (Galen Medical Journal, 2013)
Background: Anterior Cervical Discectomy and Fusion (ACDF) is an effective treatment for disc herniations; but some studies demonstrated that in the untreated levels adjacent to a fusion, increased motion might lead to an increased risk of adjacent segment degeneration (ASD). On the other hand, methods of cervical Disc Arthroplasty (CDA) have improved. The aim of this study is to evaluate and compare the rate of ASD in patients who underwent ACDF or CDA cervical spine surgery. Methods and Materials: This prospective study was performed on 84 patients with cervical radiculopathy due to single-level disc herniation referred to hospitals in Tehran, Iran from June 2011 to December 2012. All subjects were randomly allocated to Group A or Group B to undergo ACDF or CDA, respectively. The validated Neck Disability Index (NDI) questionnaire was used to assess the cervical neck pain. Results: The mean of age in Group A was 51.7 ± 9.1 years and in Group B was 49.3 ±9.2. The differences in cervical radiculopathy in the two groups were not statistically significant. The difference in mean Visual Analogue Scale (VAS) score in the two groups at each assessment time was statistically significant. Mean NDI score before the surgery was 46.9 ± 6.1 in group A, and 41.3 ±4.7 in group B. The mean NDI score improved significantly in group B. Twenty-seven of the patients in Group A experienced ASD at 12 months compared to one patient (2.3%) in Group B (p<0.05). Conclusion: According to the findings of this study, CDA leads to reduced VAS and NDI score compared to ACDF. Also increased ASD in ACDF was demonstrated when compared with CDA after 1-year follow-up.